Application of a Simple, Low-Cost, Low-Tech Method to Monitor Intertidal Rocky Shore Assemblages on a Broad Geographic Scale - Livore, Juan Pablo (2021)
Identifying susceptible regions where biodiversity changes occur at a broad geographic 11 scale or at fast rates is essential in order to protect and ameliorate affected areas. Large-12 scale coastal monitoring programs that focus on long-term variability are scarce, yet the 13 Marine Biodiversity Observation Network Pole to Pole is currently developing a 14 regional collaboration throughout the American continent collecting biodiversity data in 15 coastal habitats with a standardized systematic protocol. The use of photographic 16 methods to collect assemblage data on intertidal rocky shores can be appropriate. The 17 goal of this study was to analyze the performance of a simple, low-cost, non-destructive 18 and low-tech photographic method on a broad geographical scale ( ̴ 2000 km) of 19 Atlantic Patagonian coastline. Concurrently, we aimed to identify indicators whose 20 cover, presence or condition can be followed in time and used as beacons of change in 21 biodiversity on these rocky intertidal shores. We also explored the potential 22 relationships between assemblage structure and environmental variables, such as 23seascape classes. We identified and propose cover of mytilids, Corallina spp. and bare 24 substrate as indicators of change due to their ecological relevance in intertidal 25 assemblages and their visible and rapid response to human stressors or changes in 26 environmental conditions. Finally, we illustrate the practicality and usefulness of 27 remotely accessible environmental data, for instance the seascape classes approach as an 28 integrative tool for large-scale rocky shore studies.